Molecular genotyping of Theileria spp. detected in horses from Corrientes City, Argentina - Benitez Ibalo, Alicia P. (2025)
After the previous description and characterization of Theileria equi sensu stricto (Genotype A) in Argentina, the aim of the present study was to investigate the possible heterogeneity of 18 S rDNA genotypes circulating in this country. Therefore, blood samples from 18 horses from two different neighborhoods of Corrientes City, Corrientes Province, were analyzed for infection with Theileria species. Theileria DNA was detected in five samples (27.8%). Four nearly complete 18 S rDNA gene sequences were obtained and phylogenetic analyses were carried out. The maximum likelihood tree constructed in this study revealed that two different 18 S rDNA genotypes - namely Genotype A (T. equi sensu stricto) and Genotype C (T. equi sensu lato/Theileria haneyi) - are circulating in the same horse population. These results represent to first evidence of T. equi genotype heterogeneity in Argentina and also the first detection of a member of the T. haneyi/Genotype C group. Together with reports from Brazil, the results of this study reinforce the assumption that Genotypes A and C are the predominant genotypes in South America.